Stan wyjątkowy jako przykład stanu nadzwyczajnego w doktrynie francuskiej. Interpretacja pojęcia - Gola, Jan; Brzezińska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The basic assumption of the article was to make the characteristics of a state of emergency according to French law currently in force. For this purpose, its three key aspects were presented: historical including historical chronology of the introduction of a state of emergency, detailed scope of competence of the respective administrative services and relationships that exist between Art. 16 of the French Constitution and the provisions of the act that decrees a state of emergency. The conclusion was that, unfortunately, this instrument does not fulfill its essential role of protecting against any attack on national security.
Keywords: Francja; stan wyjątkowy; doktryna; interpretacja